Virtual Communication Competencies for Effective Virtual Pedagogy in Basic Electricity - Onwusuru, Ijeoma, Madonna; Agbo, Nnaemeka Martin2 (Online Journal for TVET Practitioners, 2024)
This study was carried out to investigate virtual communication competencies required for effective online pedagogy in Basic Electricity. Basic Electricity teachers in Anambra State are expected to possess competencies that would enable them to understand the category of students in their virtual class, choose the right channel best suitable to communicate to the class, and seek out the most suitable feedback channel within a defined time frame. Hence the need to identify the specific areas in virtual communication that Basic Electricity teachers need skills to upgrade to enhance their effectiveness in the implementation of virtual pedagogy. The study adopted a descriptive survey research design. The study was guided by a research question and one hypothesis. A five-point scale structured questionnaire was used in data collection. This was validated by three experts and the reliability was established using the Cronbach Alpha Reliability technique which yielded a reliability coefficient of 0.86. The research question was answered using mean while a statistical t-test was used to establish the significance or otherwise of the hypothesis. The findings of the study revealed that the ability to speak fluently online using voice-compliant platforms, the ability to lead discussions online, the ability to make learning interactive online, ability to make video calls, among others are the competencies to upgrade the needs of the teachers. Location was not found to be a determinant factor in the skills upgrade needed. Thus, self-development, in-house training, reflective practices, peer review, education and training-related courses as well as standardization meeting for the Basic Electricity teacher was recommended.